2018
DOI: 10.1002/ar.23916
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Lineage Analysis Does Not Provide Evidence for EMT in Adult Valve Homeostasis and Disease

Abstract: Epithelial-to-mesenchymal transition (EMT) enables stationary epithelial cells to exhibit migratory behavior and is the key step that initiates heart valve development. Recent studies suggest that EMT is reactivated in the pathogenesis of myxomatous valve disease (MVD), a condition that involves the progressive degeneration and thickening of valve leaflets. These studies have been limited to in vitro experimentation and reliance on histologic co-staining of epithelial and mesenchymal markers as evidence of EMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
(86 reference statements)
0
21
1
Order By: Relevance
“…In vitro studies with valve endothelial cells provide supporting evidence for postdevelopment EndMT capability 3 , and thus we speculated that EndMT persists at a low level throughout life in order to replenish valve interstitial cells, major producers of the valve extracellular matrix needed to insure durability and function. In contrast, EndMT is not seen in adult murine valves when analyzed by in vivo endothelial lineage tracing 4 , indicating that species, models and experimental tools are important variables. We found EndMT increased, in vivo, when ovine mitral valve leaflets were exposed to mechanical stretch designed to mimic the tethering imparted on the leaflets when the left ventricle enlarges after myocardial infarction; EndMT occurred with little evident TGFβ or leukocyte infiltration, and coincided with an increase in leaflet area 5,6 .…”
Section: Endmt In Mitral Valvesmentioning
confidence: 95%
See 1 more Smart Citation
“…In vitro studies with valve endothelial cells provide supporting evidence for postdevelopment EndMT capability 3 , and thus we speculated that EndMT persists at a low level throughout life in order to replenish valve interstitial cells, major producers of the valve extracellular matrix needed to insure durability and function. In contrast, EndMT is not seen in adult murine valves when analyzed by in vivo endothelial lineage tracing 4 , indicating that species, models and experimental tools are important variables. We found EndMT increased, in vivo, when ovine mitral valve leaflets were exposed to mechanical stretch designed to mimic the tethering imparted on the leaflets when the left ventricle enlarges after myocardial infarction; EndMT occurred with little evident TGFβ or leukocyte infiltration, and coincided with an increase in leaflet area 5,6 .…”
Section: Endmt In Mitral Valvesmentioning
confidence: 95%
“…Our understanding of EndMT has grown by leaps and bounds with the wealth of new tools and enhanced experimental capabilities. Inducible endothelial lineage tracing in murine models is particularly useful for distinguishing mesenchymal cells derived from embryonic versus post-natal EndMT 4,14 . In vitro studies complement and extend in vivo findings, and enable mechanistic experiments that can sharpen hypotheses for further testing in vivo.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Studies of canine myxomatous mitral valve disease have suggested that SMA expression is the product of endothelial-to-mesenchymal transformation (EMT) [ 43 ]. However, in mouse models of myxomatous degeneration, cell tracing experiments have not detected active EMT [ 44 ]. Therefore, we anticipate that SMA is induced by alternative mechanisms in murine mitral valve disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, this process is less controlled. While endothelial-to-mesenchymal transitions have been shown to give rise to SMA-positive cells in the embryo, fate map studies in valve disease models suggest that this process does not occur in adult valve disease [ 120 ], but it may mediate disease in canine models [ 121 ]. As there is accumulating data to suggest that the transition of qVICs to aVICs may be one of the early triggers that initiates progressive degeneration, the field has turned to understanding the mechanistic triggers.…”
Section: Ecm and Heart Valve Diseasementioning
confidence: 99%